Original paperHigh-dose-rate interstitial brachytherapy for mobile tongue cancer: preliminary results of a dose reduction trial - Akiyama, Hironori; Yoshida, Ken; Yamazaki, Hideya; Takenaka, Tadashi; Kotsuma, Tadayuki; Masui, Koji; Yoshioka, Yasuo; Arika, Takumi; Shimizutani, Kimishige; Tanaka, Eiichi (Journal of Contemporary Brachytherapy, 2014)
Purpose : To compare the outcome of our facility with another about the shortened schedule (60 Gy in 10 fractions to 54 Gy in 9 fractions) of high-dose-rate interstitial brachytherapy (HDR ISBT) for mobile tongue cancer. Material and methods : Eighteen patients were treated with HDR ISBT as a monotherapy in dose reduction schedule with some unique technique to determine the border of tumor accuracy (lugol’s staining and metal marker), and to minimize adverse effect (lead-lined silicon block) at our facility. Results: The 2-year local and regional control rates and cause-specific survival rate were 82%, 80%, and 83% and moderate to severe late complications occurred in five patients (28%), which were almost the same treatment results achieved by another facility. Conclusions : We recommend 54 Gy in 9 fractions over 7 days as a feasible treatment to reduce patient discomfort in mobile tongue cancer patients.